2008
DOI: 10.1002/pits.20333
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral profiles of children with epilepsy: Parent and teacher reports of emotional, behavioral, and educational concerns on the BASC‐2

Abstract: The Behavior Assessment Scale for Children -Second Edition (BASC-2) was administered to 108 parents and 37 teachers of children with epilepsy (mean age of 10.6 years; 51% female, 49% male). Results demonstrated high mean scores on the Atypicality, Attention Problems, Withdrawal, and Adaptive Skills scales and a high percentage of At-Risk or Clinically Significant scores on the majority of scales. Ratings were correlated with level of functioning, age of onset, and number of antiepileptic medications. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 20 publications
2
22
0
1
Order By: Relevance
“…This would include obtaining a thorough history to rule out other preexisting factors that may better explain the problems, such as associated neurological and medical conditions, developmental risk factors, psychiatric comorbidities, sleep disorders, psychosocial complications, and family history. Just as important in epilepsy populations is the need to consider epilepsy-specific factors, such as the age of onset, seizure frequency, seizure severity, and the presence of structural abnormalities on brain imaging (Dodson, 2001;Titus, Kanive, Sanders, & Blackburn, 2008). When preexisting problems can be eliminated as an explanatory factor, the likelihood of an AED being the cause of learning problems becomes more tenable.…”
Section: Treatment With Aedsmentioning
confidence: 98%
“…This would include obtaining a thorough history to rule out other preexisting factors that may better explain the problems, such as associated neurological and medical conditions, developmental risk factors, psychiatric comorbidities, sleep disorders, psychosocial complications, and family history. Just as important in epilepsy populations is the need to consider epilepsy-specific factors, such as the age of onset, seizure frequency, seizure severity, and the presence of structural abnormalities on brain imaging (Dodson, 2001;Titus, Kanive, Sanders, & Blackburn, 2008). When preexisting problems can be eliminated as an explanatory factor, the likelihood of an AED being the cause of learning problems becomes more tenable.…”
Section: Treatment With Aedsmentioning
confidence: 98%
“…Titus ve arkadaşları temporal lob epilepsisinin frontal lob epilepsisine göre daha fazla depresif belirtilerle ilişkili olduğu-nu ancak aynı farkın genel olarak fokal ve jeneralize nöbetler arasında geçerli olmadığını bulmuştur. [26] Juvenil myoklonik epilepsi üzerine yapılmış sınırlı sayıda araştırmada, depresif yakınmalar, affektif dalgalanmalar ve sosyal sorunların yüksek sıklıkta olduğu gösterilmiştir. [27,28] Mevcut literatür bilgisi toplu olarak değerlendirildiğinde nöbet tipi ve depresyon arasındaki ilişkinin çocuk ve ergenlerde daha fazla araştırmaya konu olması gerektiği göze çarp-maktadır.…”
Section: Risk Faktörleriunclassified
“…The risk for psychiatric disorders in people with epilepsy have been reported to be three to six times higher than observed in age matched apparently healthy population [1,15,18]. It has also been documented that children and adolescents with epilepsy experience more emotional and behavioural problems than healthy controls and others with chronic conditions [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 97%
“…While studies from the western world reported prevalence ranging between 23% -70.5% [4,[30][31][32][33]. Several studies have reported the negative impact of epilepsy in a child's education, perceived stigma and quality of life [4,[21][22][23][24][25][26][27][28]. The secondary impacts of caring for an epileptic child have also been reported with much social and financial burden on both the parent and the immediate society [4,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%